Pediatric peripapillary choroidal neovascularization secondary to ocular sarcoidosis: a long-term follow-up case - Zong, Yuan; Wang, Keyan; Zhang, Ting; Xu, Gezhi (BMC ophthalmology, 2025)
To describe a 14-year-old male with probable ocular sarcoidosis and bilateral peripapillary choroidal neovascularization (PCNV). We report a case of a 14-year-old boy with a 2-month history of floaters and gradual vision loss in both eyes. Examination revealed bilateral granulomatous uveitis with peripapillary subretinal lesions. The serum angiotensin-converting enzyme was elevated. Positron emission tomography demonstrated increased metabolic activity in the nasopharynx and small intestine, consistent with diagnosis of sarcoidosis. Despite resolution of vitreous cells and retinal vasculitis, the PCNV progressed slowly in the left eye, which was controlled with combined treatment of immunomodulatory regiment and multiple intravitreal anti-vascular endothelial growth factor injections over a prolonged period. This case highlights the need for a multidisciplinary approach and long-term follow-up in pediatric ocular sarcoidosis with PCNV.